Cell phone and virtuality: a systematic review - Antúnez de Mayolo, Lily Cuadros (2024)
This work is the result of the observation of the ways in which the cell phone has burst into daily life, transforming the scenario in which we lived a few decades ago. Although we recognize the benefits of this technology, due to its excessive use, worrying effects arise that we intend to evidence from the review of a set of bibliographic sources. These transformations entail risks for the coexistence among its members of the responsible for weaving values, worldview, customs, idiosyncrasies, etc. In this new reality, young people mainly establish virtual and less affective bonds. They isolate themselves from the environment, show disinterest in tangible spaces and are part of manipulable identities. The virtuality is replacing interpersonal communication. Now the definition of man as an eminently social being is fading. Our objective is to make explicit the progressive dependence of cell phones on ordinary individuals. Unprecedented ways of addressing various topics are opened. relations, social, economic, political processes. That is, technology in the personal, professional, educational spheres, etc.; “Virtualized reality” is leaving aside, among other things, soft skills: empathy, assertiveness, etc.